STORYTELLING PADA ANAK DENGAN KETERLAMBATAN PERKEMBANGAN BERBAHASA EKSPRESIF - Atika Permata Sari (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2022)
Language development in early childhood is a foundations in both mastering academic skills and social skills. Delays in early intervention will increase the risk of children experiencing problems as adults. TDB is a kindergarten student with the age of 5 years 9 months who was identified with expressive language developmental delay. The results of the assessment showed that the development of expressive language of TDB was not in accordance with its chronological age. Intelligence test results show the level of intelligence is in the category above average. The storytelling method with puppet sticks was provided to TDB for seven sessions. In each session, the researcher did storytelling using puppet stick media and then asked TDB to repeat the story that had been told by the researcher. There are seven different stories used in each session. The results of observations on the mean length of utterance show that there is an increase in the mean length of utterance from 2.3 to 3.6. This shows that the storytelling method with puppet sticks is quite effective in increasing the development of expressive language.